Relationship between Knowledge, Social Support, and Mother's Attitude towards Exclusive Breastfeeding - Sari, Ernita; Ningrum, Astika Gita; Etika, Risa (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Mother's milk (ASI) has an important role in the process of child growth and development. In achieving success of exclusive breastfeeding, of course, there are various factors that influence, including the mother's personality (knowledge and attitude) and social support from the mother's environment around . The purpose of this study was to know related between knowledge, social support and mother's attitude towards exclusive breastfeeding. This quantitative research is observational with a cross sectional approach. The total population of breastfeeding mothers in the Ngadiluwih Community Health Center is 250 people and a sample of 154 mothers was taken use a simple random sampling technique. This research held in January-March 2021. The results showed that majority of mothers gave exclusive breastfeeding by 56.5%. In addition, knowledge possessed by mothers about exclusive breastfeeding was mostly good (79.9%), social support obtained was high (54.6%), but the mother's attitude was still negative (73.4%). Chi square statistical test on the knowledge variable obtained p value = 0.002, social support p value = 0.657 while attitude variable obtained p value = 0.075. There is a significant relationship between knowledge toward exclusive breastfeeding.